STRUCTURE, POROSITY AND VOLUME MASS OF SALINE SOILS. (Multidisciplinary Journal of Science and Technology, 2025)
This article presents the results of studies devoted to the study of the effect of salinity on soil structure, porosity and mass of hajm in the conditions of medium and strong saline soils. The results of the study, the structure, porosity of the soil in the layers of 0-28, 28-40, 40-113, 113-168, 168-190 CM, as well as the mass of the hajm are given separate data on soil cuts.